2018
DOI: 10.3389/fimmu.2018.01433
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Pathway Is Essential for Glomerular Complement Activation and Proteinuria in a Mouse Model of Membranous Nephropathy

Abstract: Membranous nephropathy is an immune kidney disease caused by IgG antibodies that form glomerular subepithelial immune complexes. Proteinuria is mediated by complement activation, as a result of podocyte injury by C5b-9, but the role of specific complement pathways is not known. Autoantibodies-mediating primary membranous nephropathy are predominantly of IgG4 subclass, which cannot activate the classical pathway. Histologic evidence from kidney biopsies suggests that the lectin and the alternative pathways may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 62 publications
0
47
0
1
Order By: Relevance
“…Vivarelli et al demonstrated a predominant role of the classical pathway for neutral endopeptidase protein-associated MN [41]. In a mouse model of MN, Luo et al showed a role of the alternative pathway in the pathogenicity induced by glomerular subepithelial immune complexes [42]. However, no C3 deposition has been found in the renal tissue of mice following immunization with rabbit anti-THSD7A antibodies or purified human anti-THSD7A while these antibodies induced proteinuria and IgG deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Vivarelli et al demonstrated a predominant role of the classical pathway for neutral endopeptidase protein-associated MN [41]. In a mouse model of MN, Luo et al showed a role of the alternative pathway in the pathogenicity induced by glomerular subepithelial immune complexes [42]. However, no C3 deposition has been found in the renal tissue of mice following immunization with rabbit anti-THSD7A antibodies or purified human anti-THSD7A while these antibodies induced proteinuria and IgG deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the model can be developed rapidly and reliably. luo et al (58) found that factor B-null mice lacked glomerular deposition of c3 and c5b-9 and did not develop albuminuria. albuminuria was reduced but not completely abolished in the C5-deficient mice.…”
Section: Mouse Models Of Imn T H R O M B O S P O N D I N T Y P E -1 Dmentioning
confidence: 99%
“…Furthermore, the complement pathways of most models are unclear (Table ii). an aP is essential to complement activation in the anti-α3nc1 mouse model via factor B knockout (58). The human anti-THSd7a-related mouse model provides an opportunity to use genetic intervention in complement activation.…”
Section: Pathogenesis Of Imn: From Model To Humanmentioning
confidence: 99%
“…Mice immunized with α3(IV) collagen NC1 domain develop subepithelial immune complexes and proteinuria, recapitulating clinical and morphologic hallmarks of MN ( 54 , 55 ). In factor B −/− mice, without a functional AP, glomerular C3c and C5b–9 deposition and proteinuria were prevented, while circulating and kidney-bound IgG were unchanged ( 56 ). These findings imply that the AP is required for complement activation and proteinuria in experimental MN.…”
Section: Complement Activation In Mnmentioning
confidence: 99%